Estrategias psicopedagógicas para el control emocional en estudiantes de séptimo grado con bajo rendimiento académico - Nieto Barros, Wensther Jesús (2025)
This research aims to analyze how psychopedagogical strategies contribute to strengthening emotional control in seventh-grade students with low academic performance. The identified problem lies in the limited implementation of educational practices aimed at developing emotional skills, which negatively impacts students' motivation, concentration, and, consequently, academic performance. Many teachers do not incorporate specific strategies to promote emotional development, which leads to manifestations of inappropriate behavior, such as difficulties in interpersonal interaction, emotional dysregulation, and defiant behaviors in the classroom. The research was carried out using a qualitative approach that combined fieldwork and descriptive design. Various methods, including empirical, analytical, and deductive techniques, were employed to gather data through interviews, direct observations, and document reviews. The findings indicated that insufficient psychopedagogical strategies are linked to behaviors like impulsivity, anxiety, low self-esteem, and academic disorganization. However, when strategies that emphasize emotional support are put into practice, students demonstrate notable improvements in their self regulation skills, an increased eagerness to learn, and better relationships with their classmates. It is concluded that the use of psychopedagogical strategies has a positive impact on emotional regulation and academic performance. Therefore, it is recommended to train teachers in emotional education, integrate this content into the curriculum, promote recreational activities, and strengthen collaboration with the Student Counseling Department (DECE) to provide comprehensive support to students.